Nutrients Leaching in Response to Long-Term Fertigation and Broadcast Nitrogen in Blueberry Production - Aimé J. Messiga; Kathryn Dyck; Kiera Ronda; Kolden van Baar; Dennis Haak; Shaobing Yu; Martine Dorais (Plants, 2020)
Nutrient leaching losses from horticultural production threaten the quality of groundwater and freshwater systems worldwide. The objectives of this study were to (a) assess the effects of annual applications of ammonium sulfate fertilizer through fertigation (FERT) and broadcast (BROAD) on nutrient leaching losses and (b) determine the links among chemical property changes in leachates and soil with berry yields after 9 and 11 years of blueberry production. The long-term blueberry site was established in 2008 using seven combinations of treatments including an unfertilized control (CONT) and three N fertilizer rates (100%, 150%, 200% of recommended rates) using BROAD and FERT methods. Nutrients concentrations (NO3−-N, NH4+-N and SO42−-S) and chemical properties (pH and electrical conductivity (EC)) of leachate, sawdust and soil and berries were assessed. All FERT methods resulted in concentrations of NO3−-N in the leachates > 100 mg L−1 with a maximum of 200 mg L−1 for FERT-200 during the growing season due to the easy transport of dissolved nutrients with the irrigation water. All BROAD methods resulted into concentrations of NO3−-N in the leachates >10 mg L−1 with a maximum of 35 mg L−1 for BROAD-200 between April and July, as well as between November and April, indicating two periods of NO3−-N leaching losses. The pattern observed with BROAD indicates that irrigation water in the summer and heavy rainfall in the winter contribute to NO3−-N leaching losses. Concentrations of NH4+-N in the leachates >1 mg L−1 were measured under FERT with a peak at 64.78 mg L−1 for FERT-200, during the period April to August, due to NH4+’s ability to quickly move through the sawdust layer with irrigation water. Principal component analysis linked berry yield decrease with ammonium sulfate applications above recommended rates (FERT and BROAD) and with changes in soil pH and EC. Our results demonstrated that excess fertilizer applications above recommended rates using FERT and BROAD can threaten the sustainability of blueberry production by enhancing nutrient leaching losses and reducing berry yield.